2020
DOI: 10.1021/acs.jproteome.0c00107
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Heat Stress of Lactobacillus paracasei GCRL163 Improves Binding to Human Colorectal Adenocarcinoma HT-29 Cells and Modulates the Relative Abundance of Secreted and Cell Surface-Located Proteins

Abstract: Lactobacillus casei group bacteria improve cheese ripening and may interact with host intestinal cells as probiotics, where surface proteins play a key role. Three complementary methods [trypsin shaving (TS), LiCl−sucrose (LS) extraction, and extracellular culture fluid precipitation] were used to analyze cell surface proteins of Lactobacillus paracasei GCRL163 by label-free quantitative proteomics after culture to the mid-exponential phase in bioreactors at pH 6.5 and temperatures of 30−45 °C. A total of 416 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…( 2018 ) evaluated stress responses following transposon mutagenesis of L. paracasei after 24 hr exposure to stressors, identifying many genes not previously documented as stress-responsive and mapping which proteins were stress-specific or induced in responses to several different stimuli. We had also shown that cultivation of GCRL163 at highly growth-inhibitory temperatures, in contrast to heat shock, caused changes in relative abundance of proteins both in cytosolic extracts (Adu et al., 2018 ) and at the cell surface (Adu et al., 2020 ), suggesting that there was considerable movement of proteins to and through the cell surface and identifying regulons not previously linked with heat stress adaptation. Yu et al.…”
Section: Resultsmentioning
confidence: 91%
“…( 2018 ) evaluated stress responses following transposon mutagenesis of L. paracasei after 24 hr exposure to stressors, identifying many genes not previously documented as stress-responsive and mapping which proteins were stress-specific or induced in responses to several different stimuli. We had also shown that cultivation of GCRL163 at highly growth-inhibitory temperatures, in contrast to heat shock, caused changes in relative abundance of proteins both in cytosolic extracts (Adu et al., 2018 ) and at the cell surface (Adu et al., 2020 ), suggesting that there was considerable movement of proteins to and through the cell surface and identifying regulons not previously linked with heat stress adaptation. Yu et al.…”
Section: Resultsmentioning
confidence: 91%
“…Interestingly, proteomic studies have revealed that bile acids and heat stress resulted in their overexpression in Lc. paracasei species, leading to increased adhesion ability ( Bengoa et al, 2018 ; Adu et al, 2020 ). Several sortase genes ( srtA , strB , srtC1 , srtC2 ) were found in the genome of Lc.…”
Section: Resultsmentioning
confidence: 99%
“…Of these reagents, LiCl has been reported to be the most efficient and selective reagent for the extraction of highly hydrophobic membrane proteins (e.g., 52 kDa nonglycosylated protein) of LAB (e.g., L. helveticus ). In contrast to GHCl, LiCl has also been reported as less lethal to bacteria in the reformation and maintenance of the S-layer symmetry, indicating that LiCl has a negligible deleterious effect on the membrane integrity, as confirmed by X-ray photoelectron spectroscopy (XPS). , Surface proteins from Gram-positive bacteria are extracted using 5 M LiCl, a chaotropic agent that breaks the hydrogen bonds, disrupting the hydrophobic domains, thereby reducing the protein stability and enabling the extraction of membrane proteins. Recently, Xu et al reported a decreased concentration (1M) of LiCl during dialysis to successfully enrich membrane proteins, such as LPxTG and ABC transporters.…”
Section: Proteomic Studies In Probiotics: Progress and Accomplishmentsmentioning
confidence: 99%